U.S.-CHINA COMPETITION: IS A CHINESE CYCLE OF POWER POSSIBLE? - Mădălin-Ciprian ENESCU (Annals of the "Ovidius" University of Constanţa. Political Science Series, 2023)
The cycle of power is a theory of international relations developed by George Modelski during the Cold War in order to identify the mechanism of power transfer from one global power to another. To become a world power, a country must fulfil four conditions: a specific geography, a democracy and an open society, a leading economy, and the development of a global strategy. The last cycle of power in modern history was the American cycle, which began at the end of the Second World War and has continued until the present day, with the USSR and China as challengers. Therefore, the US-China rivalry can be seen as a case study to examine the theory of power transition and China’s potential to become a world power. China fulfils three of the four conditions proposed by George Modelski in his theory in order to become a world power, but due to the distribution of power in East Asia, China’s ability to become a world power remains extremely limited. Moreover, China’s incorporation into the international institutional architecture created by the United States is advantageous because it increases the likelihood of a peaceful transition of power between the two countries. However, despite China’s ability to create a cycle of power, it will continue to be a second-rank power in the international system, which can lead to political, social, or economic instability. As a result, it will be difficult for the Chinese leadership to create a cycle of power in the future while maintaining its political influence.